Contemporary Problems of Financing the Micro-, Small and Medium-sized Enterprises as Well as their Development - Idzik, Marcin (Współczesne problemy finansowania i rozwoju przedsiębiorstw mikro, małych i średnich, 2011)
The study presents the results of the analysis on the circumstances determinants considerations of using the external sources of financing companies’ activities. The empirical material consisted of the results of the newest, unpublished surveys among the entrepreneurs on a nationwide, representative sample of N = 1400 micro, small and medium-sized companies. The study analyzes the conditions of using the external sources of financing on the part of the supply of the credits (barriers on the part of the banks) and on the part of the demand (barriers on the part of the entrepreneurs). We conducted a segmentation of enterprises in Poland in terms of the adopted development strategies and financing of the enterprises.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 124-136
Keywords: financing enterprises; credits; development barriers; banks; management strategies